Faith and reason in the Catholic intellectual tradition - Sagut, Joel C.; Co, Alfredo P.; Aguas, Jove Jim S.; Baybado, Pablito A. Jr; Ojoy, Virgilio A.; Basas, Allan A.; Flores, Danilo R.; Sweetman, Brendan; Weckert, John (University of Santo Tomas Publishing House, 2022)
"Joel C. Sagut ruminates on the tensions between faith and reason, and their ultimate mutuality in Catholic thought. Renowned Filipino scholar Alfredo P. Co’s new work, “Doing Philosophy in the Philippines: The Thomasian Collection (1951-1959) Volume II,” was also recently released and launched alongside its first volume, which both collect scholarly articles on the condition of Filipino philosophy, and the trajectories of humanistic thought in the Catholic intellectual tradition. Joining them is “Faith and Psychology: A Walk-Through on the Filipino Basic Ecclesial Communities” by Milagros C. Arrevillaga, a close look into Philippine ecclesial communities and the psychology of communal living rooted in faith."